Strategi Peningkatan Investasi Pedesaan Dalam Meningkatkan Perekonomian Desa Di Provinsi Riau - Rahman, Khairul (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
The village is a governance structure that strengthens the State of Indonesia, in addition to the largest population in the village, livelihood was apparently made an enormous contribution to the independence of this nation. Reality is now the village is the weak link that should get the attention of government. During these rural areas are characterized among other things by the low level of labor productivity, there are still high levels of poverty, and the poor quality of rural residential environment. One way that can be done to solve some of the problems in rural areas by creating strategies that increase in rural investment to rural resource management in improving the rural economy. The main problem in this research is How the Strategy to Increase Investment in Enhancing Rural Economy Village in the province of Riau. This type of research used in this research is descriptive. This research is quantitative descriptive part of the present stage of the further observation that led to the role of statistical techniques. The location of this study covers 7 districts in Riau province namely Sengingi Regency Kuantan, Indragiri Hulu, Kampar, Pelalawan, Rokan Hulu, Rokan Hilir and Siak. Results of the study found, there is a common strategy and specific strategies to increase rural investment rural resource management in improving the rural economy